2020
DOI: 10.21203/rs.3.rs-49284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-Autophagy Axis Induces VEGFA by Peritoneal Mesothelial Cells to Promote Gastric Cancer Peritoneal Metastasis Through an Integrin α5-Fibronectin Pathway

Abstract: Background: Peritoneal metastasis (PM) is an important pathological process in the progression of gastric cancer (GC). The metastatic potential of tumor and stromal cells is governed by hypoxia, which is a key molecular feature of the tumor microenvironment. Mesothelial cells also participate in this complex and dynamic process. However, the molecular mechanisms underlying the hypoxia-driven mesothelial-tumor interactions that promote peritoneal metastasis of GC remain unclear.Methods: We determined the hypoxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…An important subtype of the integrin α chain family, ITGA5, forms heterodimers together with integrin β1 (ITGB1). Previous studies have shown that ITGA5 is overexpressed in various cancer types, where it is involved in tumor progression [ 25 28 ]. Although its role in glioma has also been reported [ 29 31 ], the corresponding upstream and downstream mechanisms of action have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…An important subtype of the integrin α chain family, ITGA5, forms heterodimers together with integrin β1 (ITGB1). Previous studies have shown that ITGA5 is overexpressed in various cancer types, where it is involved in tumor progression [ 25 28 ]. Although its role in glioma has also been reported [ 29 31 ], the corresponding upstream and downstream mechanisms of action have not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of ROS have been found to be significantly increased in patients with GC, and abnormally high levels of ROS to induce oxidative stress, which can damage the gastric mucosa and be an important factor in the development of GC [29]. In addition, hypoxia can induce autophagy and an acidic extracellular pH through intermediate components or modes, which are also associated with GC progression and chemoresistance [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Both HIF-1ɑ and HIF-2ɑ promote a more invasive phenotype [33], by activating the epithelial-mesenchymal transition (EMT) program [34][35][36] or cooperating with other strong pro-invasive factors such as Met receptor and soluble hepatocyte growth factor (HGF) [37], or VEGF receptor (VEGFR)/VEGF [38]. Notably, in triple negative breast cancer (TNBC) HIF-1ɑ stimulates the relase of the typical pro-inflammatory cytokine IL-1β that induces a metastatic attitude in both tumor cells and cancer associated fibroblasts (CAFs), creating a TME that strongly favors metastatization [39].…”
Section: Background: the Impact Of Hypoxia On Cancer And Its Microenvironmentmentioning
confidence: 99%